Transcriptome Integration Analysis at Different Embryonic Ages Reveals Key lncRNAs and mRNAs for Chicken Skeletal Muscle - Wu, Pengfei; Zhou, Kaizhi; Zhang, Jin; Ling, Xuanze; Zhang, Xinchao; Li, Peifeng; Zhang, Li; Wei, Qingyu; Zhang, Tao; Xie, Kaizhou; Zhang, Genxi (Frontiers in Veterinary Science, 2022)
The growth and development of skeletal muscle in embryonic stages are vital and it directly affects the growth performance of chickens. Long non-coding RNA (lncRNA) plays an important role in this process. In the experiment, we collected the leg muscles of fast- and slow-growing Bian chickens both at 14- and 20-day embryo ages (14E and 20E) for RNA-seq. Finally, 292 and 347 differentially expressed (DE) lncRNAs were identified in F14vsF20 and S14vsS20, and 1295 and 1560 DE mRNAs were also screened respectively. Then we constructed lncRNA-mRNA networks for the two groups respectively and found that 6 of the top 10 lncRNAs ranked with degree are same. GO analysis showed that 12 of the top 20 terms were same in the two comparison groups and most of them were related to energy metabolisms, such as cellular respiration and aerobic respiration. KEGG enrichment revealed that up to 16 pathways of the top 20 in F14vsF20 were same as that of S14vsS20 and most of them were related to growth, including citrate cycle (TCA cycle) and oxidative phosphorylation. Further analysis showed that there were 602 and 102 same DE mRNAs and DE lncRNAs between the two comparison groups. We then identified 442 lncRNA-mRNA pairs, including 201 mRNAs and 32 lncRNAs. Protein-Protein Interactions (PPI) network was predicted for the 201 mRNAs and three core networks were obtained using the plug-in MCODE of Cytoscape. Then the function of genes in the three core networks was further analyzed with ClueGo and they were mainly enriched in six groups of biological processes. On this basis, combined with KEGG pathways and lncRNA-mRNA networks, we identified several candidate lncRNAs and mRNAs. Among them, lncRNAs mainly include TCONS_00061389, TCONS_00025495, TCONS_00017622, TCONS_00216258 and TCONS_00084223, and mRNAs include PLK1, BUB1, TTK, NDUFS7 NDUFAB1, PDHA1, CDK1, SDHA, ACO2 and MDH1. The results would provide a foundation for further experiments on the role of lncRNAs in the regulation of muscle development. And it could also contribute to further clarify the regulatory mechanism of chicken skeletal muscle.